Locally Delivered Chlorhexidine Chip and Diode Laser in the Treatment of Periodontitis - Bajracharya, Alina; Shrestha, Surendra Man; Pradhan, Ameena; Regmi, Sagun (Journal of Nepalese Society of Periodontology and Oral Implantology, 2022)
Introduction: Scaling and root planing (SRP) reduces periodontal inflammation but complete removal of bacterial deposits and toxins is not always feasible. Thus, adjunctive therapeutic strategies like use of local delivery of chlorhexidine (CHX) chip and laser therapy have evolved. Objective: To compare effectiveness of locally delivered CHX chip with diode laser in treatment of periodontitis. Methods: The non-randomised trial was done in Department of Periodontics at Peoples Dental College and Hospital (PDCH) from August 2019 to July 2020 after ethical clearance from Nepal Health Research Council. Study population was patients with chronic periodontitis with bilateral periodontal pockets in contralateral hemiarches exhibiting periodontal probing depth (PPD) of ≥5-7 mm attending PDCH. Written informed consent was obtained from all participants. Baseline parameters were recorded one week after full mouth SRP. In group A CHX chip was placed and in group B diode laser treatment was done. The parameters: Oral Hygiene Index-Simplified, Plaque Index, Gingival Index, PPD, and Clinical Attachment Level (CAL) were recorded at one month, three months, and six months. Results: Fifteen patients were analysed. Comparison showed that PPD scores at one month and three months were significantly lower in Group A compared to Group B. Comparison of CAL scores at baseline of both the groups were same. At subsequent visits, CAL for Group A was lower than Group B, but mean difference was not statistically significant. Conclusions: Both groups showed significant improvements compared with baseline. However, the difference in improvement of the PPD and CAL between groups was not significant.